The maternal hair metabolome is capable of discriminating intrahepatic cholestasis of pregnancy from uncomplicated pregnancy - Yin, Nanlin; Jiang, Xiuping; Yu, Muhua; Yang, Yang; Ge, Huisheng; Han, Ting-Li; Qi, Hongbo (Frontiers in Endocrinology, 2024)
Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-specific liver disease associated with elevated bile acids in the blood. Diagnosis typically only occurs after the manifestation of clinical symptoms and the metabolic mechanisms underlying its development remain unclear.To identify the metabolic changes that occur with ICP and screen for potential biosignatures.the maternal plasma and hair metabolomes of 35 Chinese women with ICP and 42 healthy pregnancies were investigated. Plasma and hair samples, total bile acid levels (TBA), alanine transaminase levels (ALT), aspartate aminotransferase levels (AST), and additional clinical information were collected during the third trimester. The plasma and hair metabolomes were analyzed using gas chromatography-mass spectrometry. Three plasma metabolites (p < 0.05, q < 0.38) and 21 hair metabolites (p < 0.05, q < 0.05) were significantly different between ICP and healthy pregnancies. A combination of the eight most significant hair metabolites in a multivariate receiver operating characteristic curve model showed the best area under the curve (AUC) was 0.885, whereas the highest AUC using metabolites from plasma samples was only 0.74. Metabolic pathway analysis revealed 32 pathways were significantly (p and q values < 0.05) affected in the hair samples of patients with ICP. In particular, pathways associated with glutathione metabolism and ABC transporters were affected. No metabolic pathways were significantly affected in plasma. Therefore, we found that the hair metabolome was more useful than the plasma metabolome for distinguishing ICP from normal pregnancy.